2000
DOI: 10.1021/jm000199q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of Chiral Allosteric Modifiers of Hemoglobin

Abstract: A series of allosteric effectors of hemoglobin, 2-(aryloxy)-2-alkanoic acids, was prepared to investigate the effect of the stereocenter on allosteric activity. The chiral analogues were based on the lead compound, RSR13 (3b), with different alkyl/alkanoic and cycloalkyl/cycloalkanoic groups positioned at the acidic chiral center. Of the 23 racemic molecules synthesized, 5 were selected for resolution based on structure-activity relationships. One chiral analogue, (-)-(1R,2R)-1-[4-[[(3, 5-dimethylanilino)carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
(58 reference statements)
0
12
1
1
Order By: Relevance
“…This observation is in contrast to our previous structural study of deoxyHb in complex with RSR13 (1:5 molar ratio) that showed very strong RSR13 electron density 5 . Notably, other analogs of RSR13 that have amino acid substitution at the carboxylate are also characterized by weak density and/or significantly less allosteric potency than RSR13 65,66 . As will be discussed later, UPLC-MS analysis of the crystallization solution showed DD-1 to predominate the mixture, which is at least 3-fold excess over RSR13 and RSR13-CH 2 CH 2 OH combined, suggesting that the binding site may have a weaker affinity for DD-1, and thus explaining the weak presence of the effector in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is in contrast to our previous structural study of deoxyHb in complex with RSR13 (1:5 molar ratio) that showed very strong RSR13 electron density 5 . Notably, other analogs of RSR13 that have amino acid substitution at the carboxylate are also characterized by weak density and/or significantly less allosteric potency than RSR13 65,66 . As will be discussed later, UPLC-MS analysis of the crystallization solution showed DD-1 to predominate the mixture, which is at least 3-fold excess over RSR13 and RSR13-CH 2 CH 2 OH combined, suggesting that the binding site may have a weaker affinity for DD-1, and thus explaining the weak presence of the effector in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Purity was greater 90% as measured by means of LC–MS, and overall yields ranged from 31 to 42% of the theoretical values. Owing to detailed studies on the principal synthesis and series of products resulting from the employed approach,6, 8 structure confirmations using conventional strategies such as NMR or IR were not performed, and the determination of elemental compositions using high‐resolution/high‐accurate mass analyses was considered sufficient.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of efaproxiral and structural analogs was accomplished according to established procedures described elsewhere 6, 8. Briefly, 4‐hydroxyphenylacetic acid (2.6 g, 17 mmol) was converted into the corresponding acetyl chloride by reflux in 10 ml of thionyl chloride for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…xi]-2-metilpropiônico, cujo nome genérico é efaproxiral ou simplesmente RSR13, é um composto sintético (Allos Therapeutics, Denver, CO, EUA), análogo da droga clofibrato e modificador alostético da Hb, com a qual se liga de forma não-covalente através de pontes de hidrogênio e interações hidrofóbicas com três das quatro subunidades, diminuindo sua afinidade pelo O 2 [3][4][5] . Assim sendo, o RSR13 não altera a massa de hemácias, mas interfere na função da Hb, desviando para a direita a curva de dissociação da oxi-hemoglobina (HbO 2 ) de forma dose-dependente 6,7 .…”
Section: Estrutura Química E Características Biofísicasunclassified